What would Marx do? : how the greatest political theorists would solve your everyday problems - Southwell, Gareth (Firefly Books, 2018)
"When it comes to the really important questions, who better to ask than the greatest political minds in history. What Would Marx Do? uses 40 everyday questions and problems as springboards for exploring the great questions of our time, while giving you a crash course in the theories and ideas of the greatest political philosophers of all time."--Contratapa.